The Release of Nitric Oxide from S-Nitrosothiols Promotes Angiogenesis - Al-Ani, Bahjat (Public Library of Science, 2006)
BACKGROUND: Free nitric oxide (NO) reacts with sulphydryl residues to form S-nitrosothiols, which act as NO reservoirs. We sought to determine whether thiol-preserving agents and antioxidants, such as dithiothreitol (DTT) and vitamin C, induce NO release from S-nitrosylated proteins in endothelial cell cultures to promote angiogenesis. METHODOLOGY/PRINCIPAL FINDINGS: NO release was measured directly in cell supernatants using a Sievers NO Analyser, and in vitro angiogenesis was assessed by quantifying capillary-like tube network formation of porcine aortic endothelial cells (PAEC) on growth factor-reduced Matrigel. Incubation of PAEC with DTT or vitamin C significantly increased NO release in a concentration-dependent manner. However, the nitric oxide synthase (NOS) inhibitors, L-NNA and L-NIO, had no effect on DTT- or vitamin C-induced NO release, and there was no concomitant increase in the phosphorylation of endothelial NOS at serine-1177 following DTT or vitamin C treatment. DTT and vitamin C increased capillary-like tube network formation by nine- and two-fold, respectively, and the addition of copper ions doubled the effect of vitamin C. Surprisingly, DTT maintained endothelial tube networks for up to one month under serum-free conditions, and selective inhibitors of guanylyl cyclase (ODQ) and PKG (KT-5823) blocked this, demonstrating the requirement of cyclic GMP and PKG in this process. CONCLUSIONS/SIGNIFICANCE: Both DTT and vitamin C are capable of releasing sufficient NO from S-nitrosothiols to induce capillary morphogenesis. This study provides the first evidence that increased denitrosylation leads to increased bioavailability of NO, independent of NOS activity, to promote sustained angiogenesis.